Absolute scale calibration with use of excess scattering length for small‐angle X‐ray scattering. (1st April 2014) - Ohta, Noboru; Sekiguchi, Hiroshi; Sasaki, Yuji C.; Yagi, Naoto
<x xml:space="preserve">Abstract</x> For small‐angle X‐ray scattering (SAXS) in solution, absolute intensity calibration is an important step to estimate the number of electrons of the sample. In this study, the excess scattering length of 1‐bromododecane dispersed in dodecane was determined using that of 1‐chlorododecane in the same solvent. The deviation of the experimental values from theoretical calculations obtained using atomic factors was around 1%. It is suggested that the 1‐chlorododecane–dodecane system constitutes a new calibration approach that is applicable to various materials over a large energy range generally used in SAXS measurements, and could be less complex and more reliable than conventional methods.